Secondary battery and electric device
By introducing positive electrode additives of specific structures and substances into the positive electrode active material layer of lithium-ion batteries, and controlling the gaps and crack characteristics of the core and carbon cladding layers, the problems of improving circulation and rate performance and gas production risks of lithium-ion batteries are solved, and better battery performance is achieved.
Patent Information
- Application Number
- CN202411844975.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The circulation performance and rate performance of existing lithium-ion batteries need to be further improved, and other technologies to improve circulation performance lead to serious gas production problems.
The positive electrode additive of a specific structure and molar ratio and content of substance is introduced into the positive electrode active material layer, and the size of the void between the core and the carbon cladding layer of the positive electrode active material and the percentage range of the total area of cracks on the core cross-section is defined.
It achieves excellent rate performance, cycle life and storage life of lithium-ion batteries, while reducing gas production risks during internal resistance and storage.
Smart Images

Figure BDA0005189284870000151 
Figure BDA0005189284870000161 
Figure BDA0005189284870000162
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a secondary battery and an electrical device. Background Art
[0002] The rapid development of the power battery and energy storage battery industries has put forward higher requirements on the rate performance, cycle life and storage life of lithium-ion batteries.
[0003] At present, improving the rate performance, cycle life and storage life of lithium-ion batteries from the perspective of positive electrode materials, negative electrode materials, electrolytes, separators and other materials has gradually reached a bottleneck. How to further improve the performance of lithium-ion batteries without changing the positive electrode materials, negative electrode materials, electrolytes and separators has become the current research focus. Summary of the invention
[0004] The purpose of this application is to solve the problem that the cycle performance and rate performance of lithium-ion batteries in the prior art need to be further improved and that the use of other technologies to improve the cycle performance leads to serious gas production, and to propose a secondary battery and electrical device with good cycle life, storage life and rate performance, low internal resistance and low risk of gas production during storage.
[0005] To achieve the above-mentioned object, in a first aspect of the present application, a secondary battery is provided, comprising a positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector;
[0006] The positive electrode active material layer includes a lithium-containing positive electrode active material and a positive electrode additive;
[0007] The positive electrode additive comprises a core and a carbon coating layer arranged on the surface of the core;
[0008] The core includes TM, oxygen and lithium, the molar ratio of TM to oxygen is 1:(1.5-3), and the TM includes at least one of iron, cobalt, nickel, manganese and aluminum;
[0009] The mass percentage of lithium in the core is ≤21% based on the mass of lithium in the positive electrode active material;
[0010] There is a gap between the core and the carbon coating layer, and the size of the gap is 0.02 to 2 μm;
[0011] The cross section of the core has cracks, and the percentage of the total area of the cracks on the cross section is 2-50% based on the total area of the cross section of the core.
[0012] As an embodiment of the present application, based on the total area of the cross section of the core, the percentage of the total crack area on the cross section is 15-20%.
[0013] As an embodiment of the present application, the width B of the crack satisfies 20nm<B≤260nm, and the length L satisfies 0.1μm≤L≤3.2μm.
[0014] As an embodiment of the present application, based on the mass of lithium in the lithium-containing positive electrode active material, the mass percentage of lithium in the core is 2 to 15%.
[0015] As an embodiment of the present application, the thickness of the carbon coating layer is 0.01 to 0.2 μm.
[0016] As an embodiment of the present application, the average particle size of the positive electrode additive is 1 to 40 μm.
[0017] As an embodiment of the present application, in the positive electrode active material layer with an area of 100 μm×100 μm, the average number of particles of the positive electrode additive is 0.5 to 35.
[0018] As an embodiment of the present application, the core includes Li 1+x TM y O2, wherein 0<x<3, 0.35≤y<2; TM includes at least one of iron, cobalt, nickel, manganese and aluminum.
[0019] As an embodiment of the present application, the core includes Li 2.5 Fe 0.5 O2, Li2NiO2, Li3Co 0.5 O2、Li 1.33 Mn 0.67 O2 Li 2.3 Fe 0.44 Al 0.005 O2、Li 2.4 Fe 0.5 Al 0.005 O2、Li 2.35 Fe 0.48 Al 0.005 O2、Li 2.25 Fe 0.41 Al 0.005 O2、Li 2.2 Fe 0.37 Al 0.005 O2、Li 1.1 Ni 0.9 Al 0.005 O2、Li 2.3 Co 0.44 Al 0.005 O2、Li 2.6 Fe 0.6 O2、Li 2.1 Fe 0.35 Al 0.03At least one of O2.
[0020] As an embodiment of the present application, the lithium-containing positive electrode active material includes at least one of lithium iron phosphate, lithium iron manganese phosphate, a ternary material, a spinel material, and a lithium-rich manganese-based material.
[0021] In a second aspect of the present application, an electrical device is provided, comprising the secondary battery described above.
[0022] The beneficial effects of this application are:
[0023] The secondary battery provided by the present application introduces a positive electrode additive containing a specific structure, a molar ratio of a specific substance, and a specific content range of a substance into the positive electrode active material layer, and limits the size of the gap between the core of the positive electrode active material and the carbon coating layer, as well as the percentage range of the total crack area on the core cross section to the total area of the core cross section; the obtained secondary battery has excellent rate performance, cycle life and storage life, as well as low internal resistance, and can effectively reduce the risk of gas production during storage. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The cross-sectional morphology images of the positive electrode sheet in the secondary battery prepared in Example 1 at different magnifications;
[0025] Figure 2 The SEM morphology images of the positive electrode additive core in the positive electrode sheet of the secondary battery prepared in Example 1 are as follows: a-morphology image, b-calculation result image of the core crack area ratio;
[0026] Figure 3 The SEM morphology images of the positive electrode additive core in the positive electrode sheet of the secondary battery prepared in Example 16: a-morphology image, b-calculation result image of the crack area ratio of the core;
[0027] Figure 4 The SEM morphology images of the positive electrode additive core in the positive electrode sheet of the secondary battery prepared in Example 18: a-morphology image, b-calculation result image of the crack area ratio of the core;
[0028] Figure 5 The cross-sectional morphology images of the positive electrode sheet in the secondary battery prepared in Comparative Example 6 at different magnifications;
[0029] Figure 6 This is a comparison chart of the 25°C cycle performance test results of the secondary batteries prepared in Example 1 and Comparative Example 6;
[0030] Figure 7 This is a comparison chart of the test results of 60°C storage capacity retention rate of the secondary batteries prepared in Example 1 and Comparative Example 6;
[0031] Figure 8 This is a comparison chart of the normal temperature DCR test results of the secondary batteries prepared in Example 1 and Comparative Example 6;
[0032] Fig. 9 This is a comparison chart of the rate discharge performance test results of the secondary batteries prepared in Example 1 and Comparative Example 6;
[0033] Fig.10 Schematic diagram of the testing process for the void size of the core and the carbon coating. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0035] In this application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions of the listed features.
[0036] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0037] In the present application, the gap size is defined as: the vertical distance from any point on the surface of the carbon coating layer close to the inner core to the inner core surface.
[0038] It should be noted that the gap size between the inner core and the carbon coating layer refers to the average gap size of the vertical distance from any point on the surface of the carbon coating layer close to the inner core to the surface of the inner core.
[0039] In one embodiment of the present application, the present application provides a secondary battery, comprising a positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector;
[0040] The positive electrode active material layer includes a lithium-containing positive electrode active material and a positive electrode additive;
[0041] The positive electrode additive comprises a core and a carbon coating layer arranged on the surface of the core;
[0042] The core includes TM, oxygen and lithium, the molar ratio of TM to oxygen is 1:(1.5-3), and the TM includes at least one of iron, cobalt, nickel, manganese and aluminum;
[0043] The mass percentage of lithium in the core is ≤21% based on the mass of lithium in the positive electrode active material;
[0044] There is a gap between the core and the carbon coating layer, and the size of the gap is 0.02 to 2 μm;
[0045] The cross section of the core has cracks, and the percentage of the total area of the cracks on the cross section is 2-50% based on the total area of the cross section of the core.
[0046] The research of the present application found that a secondary battery provided by the present application introduces a positive electrode additive containing a specific structure, a molar ratio of a specific substance and a specific content range of substances into the positive electrode active material layer, and limits the size of the gap between the core of the positive electrode active material and the carbon coating layer, as well as the percentage range of the total area of cracks on the cross section of the core to the total area of the cross section of the core; the obtained secondary battery has excellent rate performance, cycle life and storage life, as well as lower internal resistance and low risk of gas generation during storage.
[0047] Specifically, on the one hand, the kernel contains TM and oxygen within a specific molar ratio range, and the mass percentage of lithium in the kernel is within a specific range based on the mass of lithium in the positive electrode active material, which can release lithium ions when the secondary battery is charged for the first time, provide active lithium for the secondary battery, and thus improve the cycle life and storage life of the secondary battery. On the other hand, when the size of the gap between the kernel and the carbon coating is within a specific range, and the percentage of the total crack area on the kernel cross section to the total cross section area of the kernel is within a specific range, it can effectively store part of the electrolyte, thereby improving the ion transmission in the pores of the charge and discharge positive electrode sheet, reducing the concentration polarization in the electrolyte on the surface of the positive electrode active material, improving the rate performance of the secondary battery, and reducing the internal resistance of the secondary battery. On this basis, by controlling the percentage of the total crack area on the kernel cross section to the total cross section area of the kernel, it is also possible to control the gas production of the secondary battery during storage, that is, to achieve a balance between the gas production risk and the rate performance of the secondary battery, thereby obtaining a secondary battery with excellent comprehensive effects.
[0048] It should be noted that the type of TM in the core and the molar ratio of TM to oxygen in the core are obtained through EDS testing of the cross section. Specifically, the positive electrode sheet in the secondary battery is taken and prepared by ion milling to expose the cross section of the positive electrode sheet for SEM testing; the cross section of the additive is observed by adjusting the magnification during the SEM test, and the EDS of the cross section is tested. The type of TM is obtained according to the EDS test, and the molar ratio of TM to oxygen in the core is obtained by measuring the EDS of TM and oxygen in multiple pictures and taking the average value.
[0049] Exemplarily, the molar ratio of TM to oxygen may be any point value or any two point range values within the range of 1:(1.5-3), for example, it may be one of 1:1.5, 1:1.6, 1:1.8, 1:2.0, 1:2.2, 1:2.4, 1:2.6, 1:2.8, 1:3.0 or any two range values.
[0050] In one embodiment, the molar ratio of TM to oxygen is 1:(1.8-2.4). For example, it can be one of 1:1.8, 1:1.9, 1:2.0, 1:2.1, 1:2.2, 1:2.3, 1:2.4 or any two of them. The present application found that when the molar ratio of TM to oxygen is further selected within the above range, the average valence state of TM in the additive is lower and the highly active oxygen free radicals generated by oxidation during formation charging are less, which reduces the oxidative decomposition of the electrolyte by high-valent TM and highly active oxygen free radicals during subsequent cycles and storage, thereby reducing the gas production of the secondary battery, and the overall performance of the secondary battery obtained is better.
[0051] It should be noted that the mass percentage of lithium in the core is calculated by the following formula after the ICP and gram capacity test of the positive electrode sheet and the negative electrode sheet: The mass percentage of lithium in the core and lithium in the positive electrode active material is Q1 = A1*3.861 / (C1 / E1)-1, where A1 is the sum of the mass of lithium in the positive electrode sheet per unit area and the mass of lithium in the negative electrode sheet per unit area, in g / cm 2 , A1*3.681 is the capacity corresponding to the mass of lithium in the positive electrode per unit area, and the unit is Ah / cm 2 C1 is the reversible capacity per unit area of the positive electrode, in Ah / cm 2. E1 is the first effect of the original powder of the positive electrode; for lithium iron phosphate, lithium iron manganese phosphate, and spinel materials, E1=1; for ternary materials, E1=0.891. C1 / E1 is the capacity that the lithium in the original powder of the positive electrode material can provide. Among them, A1 is obtained by testing the ICP of the positive electrode and negative electrode of a specific area after disassembling the fully discharged battery, and C1 is obtained by testing the reversible capacity of the positive electrode per unit area at 45°C and 0.04C small current after disassembling the fully discharged battery. The capacity represented by C1 is the capacity of the double-sided coated electrode. E1 is obtained by judging the type of positive electrode material based on the charge and discharge curve of the charge and discharge and the XRD of the positive electrode.
[0052] Exemplarily, based on the mass of lithium in the positive electrode active material, the mass percentage of lithium in the inner core can be any point value or any two point range values within the range of ≤21%, for example, it can be one of 0.1%, 1%, 2%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18%, 20%, 21% or any two range values.
[0053] It should be noted that the test method for the size of the gap between the core and the carbon coating layer is as follows: take the positive electrode sheet in the secondary battery and prepare a sample with an exposed cross section of the positive electrode sheet by ion milling for SEM testing, wherein the cross section is perpendicular to the surface of the sheet; find the positive electrode additive particles by adjusting the magnification during the SEM test, and observe the gap between the positive electrode additive core and the carbon coating layer; determine the test sample particles, and the specific test steps are as follows:
[0054] S1. Determine the smallest rectangle that can frame the cross section of the positive electrode additive particles.
[0055] Determine the two points (a, b) with the farthest distance between the carbon coating layers of the positive electrode additive particles, and use the connecting line of the two points as the baseline (h); translate the baseline along both sides perpendicular to the baseline until it is tangent to the outside of the carbon coating layer, and the two long sides (h1, h2) of the minimum rectangle can be obtained, and the corresponding endpoints of the two long sides can be connected to obtain the required minimum rectangle.
[0056] S2. Determine the sampling point
[0057] The two diagonals of the minimum rectangle are connected respectively to determine the center point (O) of the rectangle, and the diagonal line has four intersection points with the inner surface of the carbon coating layer; the long side and the wide side of the minimum rectangle are divided into four equal parts, that is, there are three equal division points on the two long sides and the two wide sides, a total of twelve equal division points, and the connecting line obtained by connecting the twelve equal division points with the center point of the rectangle has 12 intersection points with the inner surface of the carbon coating layer; the four intersection points of the diagonal line and the inner surface of the carbon coating layer, and the 12 intersection points of the connecting line and the inner surface of the carbon coating layer are determined as sampling points.
[0058] S3. Calculate the gap size
[0059] Measure the shortest distance from each sampling point to the kernel surface (e.g., the distance from point a1 to a2), and calculate the average value as the gap size.
[0060] Exemplarily, the gap size may be any point value or any two point range values within the range of 0.02 to 2 μm, such as 0.02 μm, 0.04 μm, 0.06 μm, 0.08 μm, 0.1 μm, 0.2 μm, 0.4 μm, 0.6 μm, 0.8 μm, 1 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, 2 μm, or any two range values. In one embodiment, the gap size is 0.2 to 1.5 μm. For example, it may be 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, or any two range values. The present application has found that when the gap size is further selected to be 0.2 to 1.5 μm, the overall performance of the secondary battery obtained is better.
[0061] It should be noted that, based on the total area of the cross section of the core, the test method for the percentage of the total crack area on the cross section is as follows: take the positive electrode sheet in the secondary battery and prepare a sample of the exposed positive electrode sheet cross section by ion milling for SEM testing, and the cross section is perpendicular to the sheet surface; observe the cracks by adjusting the magnification during the SEM test, and the crack area and cross-sectional area can be obtained by identifying the grayscale difference between the crack and the cross section of the core; then calculate it according to the formula: the percentage of the total crack area to the total cross-sectional area = total crack area / total area of the cross section of the core * 100%.
[0062] Exemplarily, based on the total area of the cross-section of the inner core, the percentage of the total crack area on the cross-section can be any point value in the range of 2 to 50% or any two points in the range, such as 2%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44%, 46%, 48%, 50%, or any two of the range values.
[0063] In one embodiment, based on the total area of the cross section of the core, the percentage of the total crack area on the cross section is 15-20%, for example, it can be one of 15%, 16%, 17%, 18%, 19%, 20% or any two of the range values.
[0064] The present application research found that the percentage of the total area of cracks on the cross section to the total area of the cross section will affect the effect of improving the rate performance of the secondary battery and reducing the internal resistance, and will also affect the stability of the positive electrode additive, specifically, it will affect the gas production and TM dissolution rate; when the total area of the cross section of the inner core is further selected, and the percentage of the total area of cracks on the cross section is 15-20%, the rate performance of the secondary battery obtained is better, the internal resistance is lower, and the gas production of the secondary battery is less; that is, the overall performance of the secondary battery obtained is better.
[0065] In one embodiment, the width B of the crack satisfies 20nm≤B≤260nm, and the length L satisfies 0.1μm≤L≤3.2μm.
[0066] It should be noted that the test method for the width and length of the crack is: after charging the secondary battery to 100% SOC, disassemble it in a drying room to obtain the positive electrode sheet, take the positive electrode sheet and prepare a sample of the exposed positive electrode sheet cross section by ion grinding for SEM testing, and the cross section is perpendicular to the surface of the sheet; observe the crack by adjusting the magnification during the SEM test, and obtain the average value of the crack width and length by measuring the size of the crack in multiple pictures.
[0067] Exemplarily, the width B of the crack may be any point value or any two point range values within the range of 20nm≤B≤260nm, for example, it may be one or any two range values of 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, 60nm, 80nm, 100nm, 120nm, 140nm, 160nm, 180nm, 200nm, 220nm, 240nm, and 260nm. The length L of the crack can be any point value or any two points in the range of 0.1μm≤L≤3.2μm, for example, it can be one of 0.1μm, 0.2μm, 0.4μm, 0.6μm, 0.8μm, 1.0μm, 1.2μm, 1.4μm, 1.6μm, 1.8μm, 2.0μm, 2.2μm, 2.4μm, 2.6μm, 2.8μm, 3.0μm, 3.2μm or any two of the range values.
[0068] The research in the present application found that the values of the width B and length L of the crack will affect the area ratio of the crack in the cross section to a certain extent, thereby affecting the comprehensive performance of the secondary battery; and the values of the width B and length L of the crack will also affect the morphology of the crack, thereby affecting the stability of the positive electrode additive. When the width B and length L of the crack are further selected within the range given in the present application, the cycle performance of the secondary battery obtained is better and the risk of gas production during storage is lower.
[0069] In one embodiment, the width B of the crack satisfies 50nm≤B≤150nm, and the length L satisfies 0.8μm≤L≤2.0μm. For example, the width B of the crack may be a range value of one or any two of 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, and 150nm. The length L of the crack may be a range value of one or any two of 0.8μm, 0.9μm, 1.0μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.7μm, 1.8μm, 1.9μm, and 2.0μm. The present application study found that when the width B and length L of the crack are further selected within the above range, the comprehensive performance of the secondary battery obtained is better.
[0070] In one embodiment, the mass percentage of lithium in the core is 2-15% based on the mass of lithium in the lithium-containing positive electrode active material. For example, it can be 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, or any two of the range values. The present application has found that when the mass percentage of lithium in the core is further selected to be within the above range, it can not only ensure that the gap size between the core and the carbon coating layer is within a suitable range and the area ratio of the corresponding cracks on the cross section is within a suitable range, but also provide a suitable active lithium supplement for the secondary battery, thereby obtaining a secondary battery with excellent rate performance and low gas production risk, and having excellent cycle and storage life.
[0071] In one embodiment, the carbon coating layer has a thickness of 0.01-0.2 μm.
[0072] It should be noted that the test method for the thickness of the carbon coating layer is: after charging the secondary battery to 100% SOC, disassemble it in a drying room to obtain the positive electrode sheet, take the positive electrode sheet and prepare a sample of the exposed positive electrode sheet cross section by ion grinding for SEM testing; observe the thickness of the additive carbon coating layer by adjusting the magnification during the SEM test, and obtain the thickness by measuring the carbon coating layer thickness in multiple pictures and taking the average value.
[0073] Exemplarily, the thickness of the carbon coating layer may be any point value or any two points in the range of 0.01 to 0.2 μm, such as one or any two of 0.01 μm, 0.02 μm, 0.04 μm, 0.06 μm, 0.08 μm, 0.1 μm, 0.12 μm, 0.14 μm, 0.16 μm, 0.18 μm, and 0.2 μm.
[0074] The research in this application found that the carbon coating layer has a certain influence on the conductivity and stability of the positive electrode additive. When the thickness of the carbon coating layer is selected within the above range, it can effectively improve the conductivity and environmental stability of the positive electrode additive. At the same time, it can also serve as a rigid shell of the positive electrode additive, and produce a specific size of gap between the inner core and the inner core when the inner core shrinks, thereby achieving the storage effect of the electrolyte, thereby improving the rate performance of the secondary battery and reducing the internal resistance of the secondary battery.
[0075] In one embodiment, based on the mass of the positive electrode additive, the mass percentage of the carbon coating layer is 0.5-5%.
[0076] Exemplarily, based on the mass of the positive electrode additive, the mass percentage of the carbon coating layer can be any point value or any two point range values in the range of 0.5 to 5%, for example, it can be 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.2%, 4.5%, 4.8%, 5% or any two of the range values.
[0077] The present application has found that when the mass percentage of the carbon coating layer in the positive electrode additive is 0.5-5%, the comprehensive performance of the secondary battery can be improved more effectively.
[0078] In one embodiment, the average particle size of the positive electrode additive is 1-40 μm.
[0079] It should be noted that the test method for the average particle size of the positive electrode additive is: take the positive electrode sheet in the secondary battery and prepare a sample with an exposed cross-section of the positive electrode sheet by ion milling for SEM testing; observe the size of the additive particles by adjusting the magnification during the SEM test, and obtain the average size of the additive particles by measuring the size of multiple pictures.
[0080] Exemplarily, the average particle size of the positive electrode additive may be any point value or any two point range values within the range of 1 to 40 μm, such as 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm or any two range values.
[0081] The research in this application found that the average particle size of the added positive electrode additive will not only affect its distribution in the positive electrode active material layer, but also affect the size of the gap between its core and the carbon coating layer after preparation and the proportion of the total crack area on the cross section; when the average particle size of the positive electrode additive is further selected to be 1 to 40 μm, the resulting secondary battery has better rate performance and cycle performance, and lower internal resistance and gas production risk.
[0082] In one embodiment, the average particle size of the positive electrode additive is 5 to 25 μm. For example, it can be 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm, 22 μm, 24 μm, 25 μm, or any two of the range values. The present application study found that when the average particle size of the positive electrode additive is further selected to be 5 to 25 μm, the comprehensive performance of the secondary battery obtained is better. In one embodiment, the average number of particles of the positive electrode additive in the 100 μm×100 μm area of the positive electrode active material layer is 0.5 to 35.
[0083] It should be noted that the test method for the average number of particles of the positive electrode additive in the 100μm×100μm area of the positive electrode active material layer is: take the positive electrode sheet in the secondary battery and prepare a sample with an exposed cross-section of the positive electrode sheet by ion milling for SEM testing; observe the number of particles of the additive by adjusting the magnification during the SEM test, and obtain the average value after measuring multiple statistics.
[0084] Exemplarily, in the area of 100 μm×100 μm of the positive electrode active material layer, the average number of particles of the positive electrode additive may be any point value or any two point range values in the range of 0.5 to 35, for example, it may be one of 0.5, 1, 2, 4, 6, 8, 10, 12, 14, 16, 18, 20, 22, 24, 26, 28, 30, 32, 35 or any two of the range values.
[0085] This application study found that the average number of particles of the positive electrode additive in the 100μm×100μm area of the positive electrode active material layer reflects the amount of positive electrode additive added to a certain extent. The addition of positive electrode additives can provide active lithium to supplement the active lithium consumed by the SEI film during the first charge of the secondary battery, thereby increasing the actual gram capacity of the positive electrode active material and thus increasing the energy density of the secondary battery; and the excess active lithium in the positive electrode additive can be temporarily stored in the negative electrode sheet to supply the consumption of active lithium by the subsequent SEI film growth, thereby improving the cycle performance and storage performance of the secondary battery. The cracks and gaps in the positive electrode additive can store electrolyte, reduce the concentration polarization on the positive electrode side during charging and discharging, thereby reducing the internal resistance of the battery and improving the rate performance.
[0086] In one embodiment, the average number of particles of the positive electrode additive in the positive electrode active material layer of 100 μm×100 μm area may be 3 to 15. For example, it may be a range of one or any two of 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15. The present application has found that when the average number of particles of the positive electrode additive in the positive electrode active material layer of 100 μm×100 μm area is further selected to be 3 to 15, the comprehensive performance of the secondary battery obtained is better.
[0087] In one embodiment, the core includes Li 1+x TM y O2, wherein 0<x<3, 0.35≤y<2; TM includes at least one of iron (Fe), cobalt (Co), nickel (Ni), manganese (Mn), and aluminum (Al).
[0088] In one embodiment, the core includes Li 2.5 Fe 0.5 O2, Li2NiO2, Li3Co 0.5 O2、Li 1.33 Mn 0.67 O2Li 2.3 Fe 0.44 Al 0.005 O2、Li 2.4 Fe 0.5 Al 0.005 O2、Li 2.35 Fe 0.48 Al 0.005 O2、Li 2.25 Fe 0.41 Al 0.005 O2、Li 2.2 Fe 0.37 Al 0.005 O2、Li 1.1 Ni 0.9 Al 0.005 O2、Li 2.3 Co 0.44 Al 0.005 O2、Li 2.6 Fe 0.6 O2、Li 2.1 Fe 0.35 Al 0.03 At least one of O2.
[0089] The present application has found that the selection of the core of the above chemical formula enables the positive electrode additive in the secondary battery prepared subsequently to include a core containing TM, oxygen and lithium, and a molar ratio of TM to oxygen of 1:
[0090] (1.5~3), and the mass percentage of lithium in the core is ≤21% based on the mass of lithium in the positive electrode active material. In addition, by selecting a substance whose core is the above chemical formula and adjusting the values of x and y, different molar ratios of TM and oxygen and the mass percentage of lithium in the core can be obtained; at the same time, the size of the gap between the core and the carbon coating layer and the proportion of the total crack area on the cross section of the core can also be controlled. In one embodiment, the lithium-containing positive electrode active material includes at least one of lithium iron phosphate, lithium manganese iron phosphate, ternary material, spinel material, and lithium-rich manganese-based material.
[0091] Exemplarily, the lithium iron phosphate includes doped or undoped lithium iron phosphate, and may or may not be coated with a carbon layer; the lithium iron manganese phosphate includes LiFe 1-x Mn x PO4, where 0 < x < 1; the ternary material includes LiNi 1-x-y Co x Mn y O2 and / or LiNi 1-x-y Co x Al y O2, where 0 < x, y < 1; the spinel material includes LiNi 2-x Mn x O4, where 0 < x ≤ 2; the lithium-rich manganese-based material includes Li 1+x TM 1-x-y Mn y O2, where 0 < x, y < 1, and TM is one or more of Ni, Co, Ti, Ru, and Cr elements.
[0092] In one embodiment, the lithium-containing cathode active material includes LiFePO4 and / or LiFe 1-x Mn x PO4, where 0 < x < 1.
[0093] It is found in the research of this application that when further selecting LiFePO4 and / or LiFe 1-x Mn x PO4, where 0 < x < 1 as the lithium-containing cathode active material, the additive can supplement the lithium consumed in the SEI during the first formation, so that more lithium ions can be embedded into the lithium vacancies in the LiFePO4 and LiFe 1-x Mn x PO4 lattice during discharge, enabling the LiFePO4 and LiFe 1-x Mn x PO4 battery to exhibit a higher specific capacity and effectively improve the energy density of the battery. And because the rate performance of LiFePO4 and LiFe 1-x Mn x PO4 itself is worse than that of the ternary material, the additive has a more significant improvement in the rate performance of LiFePO4 and LiFe 1-x Mn x PO4.
[0094] In one embodiment, the cathode active material layer further includes a conductive agent and a binder. This application places no restrictions on the conductive agent and the binder in the cathode active material layer, and any known conductive agent and binder can be used.
[0095] In one embodiment, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector; the negative electrode active material layer includes a negative electrode active material. The present application has no limitation on the negative electrode active material, and any known negative electrode active material can be used.
[0096] In one embodiment, the secondary battery further includes a separator and an electrolyte.
[0097] In one embodiment, the electrolyte includes an organic solvent, a lithium salt and an additive. The present application has no limitation on the organic solvent, lithium salt and additive in the electrolyte, and any known organic solvent, lithium salt and additive can be used.
[0098] Exemplarily, the organic solvent includes at least one of ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl methyl carbonate, and dimethyl carbonate; the lithium salt includes at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, and lithium bis(trifluoromethylsulfonyl)imide; and the additive includes at least one of a film-forming additive, a conductive additive, and a flame retardant additive.
[0099] In one embodiment, the separator of the secondary battery is disposed between the positive electrode and the negative electrode.
[0100] In one embodiment of the present application, the present application proposes an electrical device, and the electrical device includes the secondary battery described in the present application.
[0101] Exemplarily, the above-mentioned electrical devices may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0102] Example 1
[0103] The present invention provides a secondary battery, wherein a method for preparing the secondary battery comprises the following steps:
[0104] (1) Preparation of positive electrode sheet
[0105] The positive electrode additive (core is Li 2.5 Fe 0.5O2, carbon coating layer thickness 0.1μm) and positive electrode active material (lithium iron phosphate) are mixed at a mass ratio of 1.5:100 to obtain a mixture, the mixture, conductive agent (super P and carbon nanotubes in a mass ratio of 1:1) and binder (polyvinylidene fluoride) are mixed at a mass ratio of 96:2:2, and solvent N-methylpyrrolidone (NMP) is added to stir in a vacuum mixer to obtain a uniform positive electrode slurry. The positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, dried at 100°C after coating, and then rolled, slit and cut to obtain a positive electrode sheet;
[0106] (2) Preparation of negative electrode sheet
[0107] The negative electrode active material (graphite), conductive agent (super P), carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) are mixed in a mass ratio of 97:1:1:1, and deionized water is added to stir in a vacuum mixer to obtain a uniform negative electrode slurry. The negative electrode slurry is evenly coated on the negative electrode current collector copper foil, dried at 100°C after coating, and then rolled, slit and cut to obtain a negative electrode sheet;
[0108] (3) Preparation of electrolyte
[0109] The organic solvent is a mixed solution containing ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC), wherein the volume ratio of EC, EMC and DEC is 30:40:30. In an argon atmosphere glove box with a water content of <10ppm, fully dried electrolyte salt LiPF6 is dissolved in the organic solvent to a concentration of 1 mol / L, and then 2wt.% of fluoroethylene carbonate (FEC) is added to prepare an electrolyte;
[0110] (4) Preparation of secondary batteries
[0111] The positive electrode sheet, the separator, and the negative electrode sheet are wound or stacked in order, so that the separator is just between the positive and negative electrodes to isolate the two electrodes, and then the roll core is put into the aluminum plastic film, baked to remove moisture, and then the electrolyte is injected after baking, and then sealed, hot and cold pressed, formed, sealed and divided to obtain a secondary battery;
[0112] Among them, the cross-sectional morphology of the positive electrode sheet after disassembly of the secondary battery prepared in Example 1 at different magnifications is as follows Figure 1 As shown; the SEM morphology of the core of the positive electrode additive in the positive electrode sheet is as follows Figure 2 As shown, Figure 2 In the figure, a is the morphology diagram, and b is the calculation result diagram of the core crack area ratio.
[0113] Embodiments 2 to 5
[0114] The present invention provides a secondary battery. The difference between the preparation method of the secondary battery and that of the embodiment 1 is that the positive electrode additive core Li is adjusted. 1+x TM y The values of x and y in O2 achieve the change of the molar ratio of TM and oxygen.
[0115] Embodiment 6-7
[0116] The present invention provides a secondary battery. The difference between the preparation method of the secondary battery and that of the embodiment 1 is that the positive electrode additive core Li is adjusted. 1+x TM y The selection of TM in O2 implements the change of TM type.
[0117] Embodiments 8 to 11
[0118] The embodiment of the present application provides a secondary battery. The difference between the preparation method of the secondary battery and that of embodiment 1 is that the average amount of the positive electrode additive is adjusted to achieve the change of Q1.
[0119] Embodiments 12 to 15
[0120] The embodiment of the present application provides a secondary battery. The difference between the preparation method of the secondary battery and that of embodiment 1 is that the particle size of the positive electrode additive is adjusted to achieve a change in the size of the voids.
[0121] Embodiments 16 to 18
[0122] The present invention provides a secondary battery. The difference between the preparation method of the secondary battery and that of the embodiment 1 is that the positive electrode additive core Li is adjusted. 1+x TM y The amount of Al doping at the TM position in O2 achieves the change of Q2;
[0123] Among them, the SEM morphology images of the positive electrode additive core in the positive electrode sheet after the secondary batteries prepared in Example 16 and Example 18 are respectively as follows: Figures 3-4 As shown; the SEM morphology of the core of the positive electrode additive in the positive electrode sheet is as follows Figure 2 As shown, Figure 2 In the figure, a is the morphology diagram, and b is the calculation result diagram of the core crack area ratio.
[0124] Embodiments 19 to 20
[0125] The present invention provides a secondary battery. The difference between the preparation method of the secondary battery and that of the embodiment 1 is that the positive electrode additive core Li is adjusted. 1+x TM y The values of x and y in O2 and the amount of Al doping at the TM position can change the crack width and length.
[0126] Examples 21-22
[0127] The embodiment of the present application provides a secondary battery. The difference between the preparation method of the secondary battery and that of embodiment 1 lies in that the preparation process of the positive electrode additive is adjusted to achieve changes in the thickness of the carbon coating layer and Q3.
[0128] Embodiments 23-24
[0129] The embodiment of the present application provides a secondary battery. The difference between the preparation method of the secondary battery and that of the embodiment 1 is that the positive electrode active material is adjusted to achieve a change in the type of the positive electrode active material.
[0130] Comparative Examples 1-2
[0131] The comparative example of the present application provides a secondary battery. The difference between the preparation method of the secondary battery and that of Example 1 is that the positive electrode additive core Li is adjusted. 1+x TM y The values of x and y in O2 and the amount of Al doping at the TM position achieve the change in the molar ratio of TM and oxygen.
[0132] Comparative Example 3
[0133] The comparative example of the present application provides a secondary battery. The difference between the preparation method of the secondary battery and that of Example 1 is that the average amount of the positive electrode additive is adjusted to achieve the change of Q1.
[0134] Comparative Examples 4-5
[0135] The comparative example of the present application provides a secondary battery. The difference between the preparation method of the secondary battery and that of Example 1 is that the particle size of the positive electrode additive is adjusted to achieve a change in the size of the voids.
[0136] Comparative Example 6
[0137] The comparative example of the present application provides a secondary battery, the preparation method of the secondary battery is different from that of Example 1 in that no positive electrode additive is added;
[0138] Among them, the cross-sectional morphology of the positive electrode sheet after disassembly of the secondary battery prepared in Comparative Example 6 at different magnifications is as follows Figure 5 shown.
[0139] Comparative Example 7
[0140] The difference between Comparative Example 7 and Comparative Example 6 is that the positive electrode active material is LiMn 0.0.6 PO4;
[0141] Comparative Example 8
[0142] The difference between Comparative Example 8 and Comparative Example 6 is that the positive electrode active material is LiNi 0.6 Co0.2 Mn 0.2 O2.
[0143] In the secondary batteries prepared in the embodiments and comparative examples, the type of the core TM and its molar ratio to oxygen, the mass percentage of lithium in the core Q1 based on the mass of lithium in the positive electrode active material, the size of the gap between the core and the carbon coating layer, the percentage of the total area of the crack on the cross section Q2 based on the total area of the cross section of the core, the width B and length L of the crack on the cross section of the corresponding core, the thickness of the carbon coating layer, the mass percentage of the carbon coating layer Q3 based on the mass of the positive electrode additive, the particle size of the positive electrode additive, the average number of particles of the positive electrode additive in the 100μm×100μm area of the positive electrode active material layer Q4, the chemical formula of the core, and the type of lithium-containing positive electrode active material are shown in Tables 1 to 2;
[0144] Table 1 Parameters of secondary batteries
[0145]
[0146]
[0147] Table 2 Parameters of secondary batteries
[0148]
[0149]
[0150] The performance tests of the secondary batteries prepared in the examples and comparative examples are as follows:
[0151] 1. Cycle performance: 1C / 1C cycle charge and discharge test is carried out in a 25℃ hot room, constant current and constant voltage charging, current is 1C, cut-off current is 0.05C, constant current discharge current is 1C; 5min is left between the charge and discharge steps, and the charge and discharge voltage range depends on the type of positive electrode material, such as 2.5~3.65V for lithium iron phosphate, 2.5~4.25V for lithium iron manganese phosphate, 2.8~4.3 / 4.35 / 4.4 / 4.45V for medium nickel ternary materials, and 2.8~4.1 / 4.15 / 4.2 / 4.25V for high nickel ternary materials; the cycle capacity retention rate is calculated as follows: cycle retention rate of the Xth cycle = (discharge capacity of the Xth cycle - discharge capacity of the first cycle) / discharge capacity of the first cycle * 100%;
[0152] 2. Storage performance: Test the 1C capacity of the battery at 25°C and fully charge it. After fully charging, store the battery in a 60°C oven. After storing for a certain number of days, take the battery out and measure the 1C recovery capacity at 25°C and fully charge it. Repeat the above steps. Test the capacity every 15 days in the first 60 days, and test the capacity every 30 days after 60 days. The storage capacity retention rate is calculated as follows: Storage X Days Capacity Retention Rate = (Storage X Days Discharge Capacity - Storage 0 Days Discharge Capacity) / Storage 0 Days Discharge Capacity * 100%;
[0153] 3. DCR test: At 25℃, according to the 1C capacity of the battery, adjust the battery to 90% SOC, 50% SOC and 20% SOC in turn, and after leaving it for 60 minutes, execute the 5C discharge pulse 10s program. Calculate DCR based on the starting voltage, ending voltage and pulse current of the discharge pulse. The DCR calculation formula is as follows: DCR = (pulse starting voltage - pulse ending voltage) / pulse current;
[0154] 4. Rate performance: Charge the battery at 1C constant current and constant voltage (cut-off current is 0.05C), and then discharge at 0.33C / 0.5C / 1C / 2C / 3C / 4C constant current to obtain the discharge capacity of the battery at different rates, and calculate the capacity retention rate of rate discharge. The calculation formula for the rate discharge capacity retention rate is as follows: XC rate discharge capacity retention rate = (XC discharge capacity - 0.33C discharge capacity) / 0.33C discharge capacity * 100%; (XC is the corresponding rate)
[0155] 5. 0% SOC storage gas generation test: The battery was adjusted to 0% SOC using 1C current at 25°C, and the battery was stored in an oven at 70°C. The volume of the secondary battery was tested using the drainage method every other day to obtain the volume expansion rate of the secondary battery after 4 days of storage; volume expansion rate = (volume after 4 days of storage - initial volume) / initial volume * 100%;
[0156] The results obtained are shown in Table 3;
[0157] Table 3 Performance test table of secondary batteries
[0158]
[0159]
[0160] It can be seen from Table 3 that the comprehensive performance of the secondary battery obtained by adopting the technical solution provided by the present application is excellent. For the system in which the positive electrode active material is lithium iron phosphate, the system of lithium iron manganese phosphate, and the system of ternary, the comprehensive performance of the secondary battery is improved; specifically, for the system in which the positive electrode active material is lithium iron phosphate, the internal resistance is low, and the 50% SOC DCR is below 26.8mΩ; the rate performance is excellent, and the 4C rate discharge retention rate is above 76.8%; the cycle performance is excellent, the 25°C cycle capacity retention rate is above 91.3%, and the 60°C cycle capacity retention rate is above 82.5%; the storage gas production risk is low, and the volume expansion rate after 4 days of storage is below 21.0%; it can be seen from Examples 1 to 22 and Comparative Examples 1 to 6 that when the provided technical solution is not within the scope given in the present application, the effect of the present application cannot be achieved; this point can be seen from the performance test results of the secondary batteries prepared in Example 1 and Comparative Example 6 Figures 6 to 9 It can also be seen intuitively in .
[0161] Finally, it should be noted that the above embodiments are intended to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, a person of ordinary skill in the art should understand that the technical solution of the present application may be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.
Claims
1. A secondary battery, comprising a positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, characterized in that: The positive electrode active material layer includes a lithium-containing positive electrode active material and a positive electrode additive; The positive electrode additive comprises a core and a carbon coating layer arranged on the surface of the core; The core includes TM, oxygen and lithium, the molar ratio of TM to oxygen is 1:(1.5-3), and the TM includes at least one of iron, cobalt, nickel, manganese and aluminum; The mass percentage of lithium in the core is ≤21% based on the mass of lithium in the positive electrode active material; There is a gap between the core and the carbon coating layer, and the size of the gap is 0.02 to 2 μm; The cross section of the core has cracks, and the percentage of the total area of the cracks on the cross section is 2-50% based on the total area of the cross section of the core.
2. The secondary battery according to claim 1, characterized in that: Based on the total area of the cross section of the core, the percentage of the total crack area on the cross section is 15-20%.
3. The secondary battery according to claim 1, characterized in that: The width B of the crack satisfies 20nm≤B≤260nm, and the length L satisfies 0.1μm≤L≤3.2μm.
4. The secondary battery according to claim 1, characterized in that: The mass percentage of lithium in the core is 2-15% based on the mass of lithium in the lithium-containing positive electrode active material.
5. The secondary battery according to claim 1, characterized in that: The thickness of the carbon coating layer is 0.01-0.2 μm.
6. The secondary battery according to claim 1, characterized in that: The average particle size of the positive electrode additive is 1 to 40 μm.
7. The secondary battery according to claim 1, characterized in that: In the positive electrode active material layer with an area of 100 μm×100 μm, the average number of particles of the positive electrode additive is 0.5 to 35.
8. The secondary battery according to claim 1, characterized in that: The core includes Li 1+x TM y O2, Among them, 0<x<3, 0.35≤y<2; TM includes at least one of iron, cobalt, nickel, manganese and aluminum.
9. The secondary battery according to claim 8, characterized in that: Li 2.5 Fe 0.5 O2、Li2NiO2、Li3Co 0.5 O2、Li 1.33 Mn 0.67 O2 Li 2.3 Fe 0.44 Al 0.005 O2、Li 2.4 Fe 0.5 Al 0.005 O2、Li 2.35 Fe 0.48 Al 0.005 O2、Li 2.25 Fe 0.41 Al 0.005 O2、Li 2.2 Fe 0.37 Al 0.005 O2、Li 1.1 Nor 0.9 Al 0.005 O2、Li 2.3 Co 0.44 Al 0.005 O2、Li 2.6 Fe 0.6 O2、Li 2.1 Fe 0.35 Al 0.03 O2 is a source of oxygen.
10. The secondary battery according to claim 1, characterized in that: The lithium-containing positive electrode active material includes at least one of lithium iron phosphate, lithium iron manganese phosphate, ternary materials, spinel materials, and lithium-rich manganese-based materials.
11. An electrical device, characterized in that: The invention comprises the secondary battery according to any one of claims 1 to 10.
Citation Information
Patent Citations
Positive electrode sheet, preparation method thereof, lithium ion battery and vehicle
CN110729451A
Lithium supplement additive for core-shell positive electrode as well as preparation method and application of lithium supplement additive
CN115692698A
Lithium-rich composite material and preparation method and application thereof
CN117293317A
Positive pole piece, secondary battery, battery pack and electric equipment
CN117712283A
Secondary battery and electric device
CN119050447A